Bisphenols and Leydig Cell Development and Function - Li, Xiaoheng; Wen, Zina; Wang, Yiyan; Mo, Jiaying; Zhong, Ying; Ge, Ren-Shan (Frontiers in Endocrinology, 2020)
Bisphenol A (BPA) is a ubiquitous environmental pollutant that comes mainly from the manufacture and use of plastics and the degradation of industrial plastics-related wastes. Evidence from experimental animals and human studies supports the notion that BPA produces endocrine disrupting effects on Leydig cell development and function. In order to better understand the adverse effects of BPA, we reviewed its action and mechanisms by analyzing in vivo and in vitro rodent data and human epidemiological evidence. Apparently, BPA has estrogenic and anti-androgenic effects, thus disrupting Leydig cell development and function, causing the related reproductive disorders, such as Testicular Dysgenesis Syndrome, delay of puberty, and subfertility/infertility. Increasing use of BPA analogues due to the restriction of BPA production has also raised concerns for these new chemicals. They might share the similar or different actions and mechanisms from BPA.